2017
DOI: 10.1093/jee/tox332
|View full text |Cite
|
Sign up to set email alerts
|

New Insight into the Management of the Tomato Leaf Miner, Tuta absoluta (Lepidoptera: Gelechiidae) with Entomopathogenic Nematodes

Abstract: The tomato leaf miner, Tuta absoluta (Meyrick) (Lepidoptera: Gelechiidae), is a serious threat to tomato production in the world. Due to serious issues with insecticide resistance, there is a dire need for alternative control methods. Entomopathogenic nematodes (EPN) have potential for the biological control of T. absoluta. In the laboratory, we examined the effect of temperature, soil type, and exposure time on the efficacy of the EPN species Steinernema carpocapsae (Nematoda: Steinernematidae) and Heterorhab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 46 publications
0
26
1
Order By: Relevance
“…The highest pathogenicity of EPN isolates belonging to Steinernema genus than Heterorhabditis had also been reported by Batalla-carrella et al (2010) who obtained 76.3% mortality of T. absoluta larvae inside the leaf galleries using H. bacteriophora, while it was 88.6 and 92.0%, using S. carpocapsae and S. feltiae, respectively, at a dosage of 60 IJs/cm 2 . Furthermore, Steinernema genus was observed to be the most virulent among different EPN species by different other researchers (Van Damme et al 2016;Mutegi et al 2017, andKamali et al 2018) which is inconsistent with the obtained findings.…”
Section: Resultscontrasting
confidence: 57%
See 1 more Smart Citation
“…The highest pathogenicity of EPN isolates belonging to Steinernema genus than Heterorhabditis had also been reported by Batalla-carrella et al (2010) who obtained 76.3% mortality of T. absoluta larvae inside the leaf galleries using H. bacteriophora, while it was 88.6 and 92.0%, using S. carpocapsae and S. feltiae, respectively, at a dosage of 60 IJs/cm 2 . Furthermore, Steinernema genus was observed to be the most virulent among different EPN species by different other researchers (Van Damme et al 2016;Mutegi et al 2017, andKamali et al 2018) which is inconsistent with the obtained findings.…”
Section: Resultscontrasting
confidence: 57%
“…Here, EPNs belonging to Steinernema genus were more effective than the ones belonging to Heterorhabditis ( Table 2). Kamali et al (2018). The local EPN isolates were able to kill T. absoluta and had even been found to be effective against white grubs in Rwanda (Kajuga et al 2018), while it was not easy to find EPNs which can kill them (Laznik and Trdan, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…As for desiccation tolerance, nematodes have different thermal limits and optima depending on their species [ 43 , 44 , 62 ]. Temperature is probably the most important factor impacting EPN efficacy [ 23 , 25 , 38 , 48 , 51 , 63 , 64 ]. Temperature can also be used as a tool to improve EPN efficacy.…”
Section: Trait Diversitymentioning
confidence: 99%
“…The method of cover and placement of EPNs on open surfaces (like foliar habitats) is critical, as humidity, exposure to ultraviolet light and temperature are not buffered, in contrast to those that are experienced in soil environments (Wright et al, 2005;Dito et al, 2016). The use of EPNs has been successfully implemented as a control strategy for two leaf-mining lepidopteran pests, namely the tomato leaf miner, Tuta absoluta (Meyrick) (Gelechiidae) (Batalla-Carrera et al, 2010;Gözel & Kasap, 2015;Van Damme et al, 2015;Kamali et al, 2017;Mutegi et al, 2017) and the citrus leaf miner, Phyllocnistis citrella Stainton (Gracillariidae) (Beattie et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies undertaken so far on leaf-mining Lepidoptera have focused on the use of steinernematids. These studies have identified Steinernema affine Wouts, Mráček, Gerdin & Bedding (Gözel & Kasap, 2015), Steinernema carpocapsae Wouts, Mráček, Gerdin & Bedding (Beattie et al, 1995;Batalla-Carrera et al, 2010;Gözel & Kasap, 2015;Van Damme et al, 2015;Kamali et al, 2017), Steinernema feltiae (Filipjev) Wouts, Mráček, Gerdin & Bedding (Batalla-Carrera et al, 2010;Gözel & Kasap, 2015;Van Damme et al, 2015), and Steinernema karii Waturu, Hunt & Reid (Mutegi et al, 2017) as successful biological control agents against a variety of leaf-mining insects. Heterorhabditis bacteriophora Poinar has been used in an attempt to control T. absoluta pest populations, although success has only been achieved under greenhouse conditions (Batalla-Carrera et al, 2010;Gözel & Kasap, 2015;Kamali et al, 2017).…”
Section: Introductionmentioning
confidence: 99%